A Feasibility Study on the Establishment of Wood Polish in Ph1 Bagong Silang (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researchers made this product because we found out that using lemon and olive oil or from natural resources is a big help to our everyday life, it aims to create a free toxic product that would help to avoid harmful from chemical therefore Alleha wood polish is aim to give you the best and satisfying product. The researchers used survey method in conducting study. It is because the said method is the easiest way in gathering information to validate the viability of new innovated product. The researchers found out that majority of the respondents accept the new innovated product. The other competitors did, both giving leaflets and posting on social media got the highest rank with 30% followed by posting posters with 20%. Lastly, billboard got the lowest rank with 10%. And when it comes to the Product price, the answer YES got the highest rank with 100% then the answer NO got the lowest rank with 0%. Alleha Wood Polish use organic ingredients so it cannot be harmful to your skin. On the other hand, the proponents put nice smell of fragrance to it that will enjoy of the consumers. Other brands have the smell of engined oil that is irritating, depressing and other bad moods can be the response to it’s used the said product. Meanwhile the other brands used a lot of chemical to their products so it's surely harmful. We know that chemicals are not good to our health. So that the researchers decided to use organic ingredients because it's all made of natural resources, because some of the user are having skin irritations when the product mistakenly put into their skin.
Keywords: wood polish, feasibility, BCP